PENGARUH MODAL MANUSIA TERHADAP KEBERHASILAN USAHA MELALUI INOVASI PRODUK (Survei Pada UMKM Industri Kreatif Sub Sektor Industri Pasar Barang Seni Lukisan Tangan Kelurahan Jelekong Kab.Bandung) - Diana Puspa, - (2020)
The painting craft industry in Jelekong Village is a creative industry sub-sector of the leading hand painting art market in Bandung Regency. However, the superiority of the painting industry has not been able to show high business success. This condition is related to human capital and product innovation owned by the business actors. This study aims to determine the level of human capital, product innovation and business success as well as how the influence of human capital on business success through product innovation in the creative industries of the hand painting art market industry sector in Jelekong Village, Bandung Regency. The method of the research is descriptive verificative which investigate the whole population taken as sample consisting of totally 34 painting craft industry entrepreneurs. The type of research used in this study is the census. The results showed that human capital, product innovation and business success is in the high category. Partially, human capital has no effect on business success, human capital has an effect on product innovation and product innovation has an effect on business success. While simultaneously (simultaneous) human capital variables significantly positive effect on business success through product innovation. Keywords: Human Capital, Business Success, Product Innovation